The method of active protection of information from the laser acoustic intelligence systems - Катаєв, Віталій Сергійович; Яремчук, Юрій Євгенович (Ukrainian Information Security Research Journal, 2019)
In this paper, we analyzed the optoelectronic technical channel of information leakage and Laser Spy System, analyze the threats which they make and offer solutions to existing information security issues. The Laser Spy System is considered by many to be the Holy Grail of high tech spy devices because it can give the user the ability to listen in on conversations that take place in a distant building without having to install a bug or transmitter at the location. The Laser Spy System was said to be invented in the Soviet Union by Leon Theremin in the late 1940s. Using a non-laser based infrared light source, Theremin's system could detect sound from a nearby window by picking up the faint vibrations on the glass surface. The KGB later used this device to spy on the British, French and US embassies in Moscow. The Laser Spy System goes by several names such as the Laser Microphone, Laser Listener, Laser Bug, Window Bounce Listener and a few similar names. The Laser Spy certainly works well under ideal conditions, but it has many strengths and weaknesses that will be discussed in this paper. General component in the Laser Spy system is the laser, which will target a distant reflective object and send the beam back to your receiver for decoding. When the laser reflects from the target window, the slight vibrations from conversations or noise that vibrate the windows cause a very slight change in position of the returning laser beam. These changes in the laser fluctuations are taken by a phototransistor and then converted into sound. The most common methods and means of protection are presented, these methods can be both active and passive, but they all have a number of shortcomings, such as high cost, the creation of acoustic noise, insufficient protection, etc. We are proposed the method of laser noise as an alternative to the existing one, and the concept of its implementation is given. This method is based on the creation of counter laser radiation. This radiation consists of a plurality of laser beams that have parameters that are similar to the parameters of the rays of the attacker. Experiments have shown that the interception of the reflected laser beam is complicated if anti-radiation is applied.